Differentiated Integration at Work: The Institutionalisation and Implementation of Opt-Outs from European Integration in the Area of Freedom, Security and Justice - Tekin, Funda (Nomos Verlagsgesellschaft mbH & Co. KG, 2012)
With the increasing heterogeneity among EU Member States the concept of differentiated integration has become a reality. Particularly EU policy fields that touch upon core sovereignty rights of the nation state, such as the Area of Freedom, Security and Justice, give evidence of a variety of flexible and differentiated integration.The present book substantially extends the research that acknowledges differentiation to form EU-integration-reality. Based on a profound treaty analysis the term differentiated integration is unearthed from the semantic avalanche of (inter)related concepts. Building on this definition, an in-depth and thorough analysis of the implementation of the British, the Irish and the Danish opt-outs in the AFSJ generates insights on the functional and structural patterns of integration that result from the interplay of institutionalisation and implementation of opt-outs. To this end the analytical frame of the paths of differentiated integration at work has been developed by mutually fusing assumptions of historical institutionalism and of an extended version of differentiated integration theory. Furthermore, the book takes the reader on an expedition through the different facets and particularities of the AFSJ drawing a concise picture of its complex provisions, its incomplete communitarisation and the inter-linkage of its policies.